The history of infectious disease: an overview and warning - Smocovitis, Vassiliki Betty (Henry Stewart Talks, 2022)
History of infectious disease, Emerging pathogens, Zoonotic disease, Epidemics come in waves, Cultural responses to infectious disease, Infectious diseases overview from Hansen’s disease till SARS-CoV-2, Biodiversity loss, Industrial farming, Population demographics